Effect of seminal plasma on Atlantic salmon (Salmo salar) sperm vitrification - Figueroa, E.; Merino, O.; Risopatron, J.; Isachenko, V.; Sanchez, R.; Effer, B.; Isachenko, E.; Farias, J. G.; Valdebenito, I. (ELSEVIER SCIENCE INC, 2015)
This study was designed to test a vitrification method in Atlantic salmon spermatozoa and determine the capacity of seminal plasma (SP) to protect these cells from cryoinjuries. The vitrification medium consisted of a standard buffer for fish spermatozoa (Cortland medium) + 10% DMSO + 2% BSA + 0.13-M sucrose + SP at concentrations of 30% (G30), 40% (G40), or 50% (G50). Fresh sperm was used as a control. To freeze the samples, 30-mu L suspensions of spermatozoa from each group were dropped directly into liquid nitrogen. The resulting spheres were placed in cryotubes for storage in liquid nitrogen. The cryotubes with the vitrified spermatozoa were thawed by placing them in a water bath at 37 degrees C for 45 seconds. After thawing, the following sperm quality parameters were determined by flow cytometry: DNA fragmentation (terminal deoxynucleotidyl transferase dUTP nick end labeling), plasma membrane integrity (SYBR-14/PI, staining technique), and mitochondrial membrane potential (JC-1 staining). An optical microscope was used to assess subjectively sperm motility, whereas fertility was determined by the presence of neurulation using five replicates per treatment in a sample of 30 eggs. Spermatozoa quality variables were preserved best when the highest concentration of SP (50%) was used (DNA fragmentation, 9.2%; plasma membrane integrity, 98.6%; mitochondrial membrane integrity, 47.2%; motility, 44.1%; and fertility, 46.2%). (C) 2015 Elsevier Inc. All rights reserved.